Prevalence and distribution of left ventricular diastolic dysfunction in treated patients with long-lasting hypertension. (2nd November 2018) - Świerblewska, Ewa; Wolf, Jacek; Kunicka, Katarzyna; Graff, Beata; Polonis, Katarzyna; Hoffmann, Michał; Chrostowska, Marzena; Szyndler, Anna; Bandosz, Piotr; Graff, Beata; Narkiewicz, Krzysztof
Abstract: Background: Although the presence of sub-clinical left ventricular diastolic dysfunction (LVDD) increases cardiovascular risk, the current ESH/ESC guidelines do not include the presence of this condition in the list of target organ damage or cardiovascular risk charts dedicated to the hypertensive population. Several conditions may predict the LVDD occurrence, however, clustering of these factors with hypertension makes the relationship less clear. Therefore, the aim of this study was to evaluate both the occurrence and the severity of diastolic dysfunction in a large cohort of treated hypertensives. Methods: We retrospectively analyzed records of 610 hypertensive participants of the CARE NORTH Study who consented to echocardiography and were free of overt cardiovascular disease. Mean age was 54.0 ± 13.9 years (mean ± SD), BMI 29.7 ± 4.8 kg/m 2 . The exclusion criteria were: established heart failure, LVEF <45%, coronary revascularization, valvular defect, atrial fibrillation, or stroke. The staging of LVDD was based on comprehensive transthoracic echocardiographic measurements. Results: 49.7% percent of the patients had normal diastolic function (38.8% vs. 59.0%, females (F) vs. males (M), respectively; p  < .001). Grade 1 LVDD was documented in 24.4% (27.8% and 21.6%; F and M; p  = .08) and grade 2 LVDD in 19.3% (24.9% and 14.6%; F and M; p  = .001) of the patients. None were diagnosed with grade 3 LVDD. In the logistic regression model, female sex, advancing age, obesity status, established diabetes mellitus, higher 24-hour SBP, and increasing LVMI were identified as the independent variables increasing the odds for the presence of LVDD, whereas blood-lowering therapy attenuated the risk. Conclusions: There is an unexpectedly high prevalence of different forms of diastolic dysfunction in treated hypertensive patients who are free of overt cardiovascular disease.